Biochanin A enhances type H vessel formation and improves epiphysis deformities following ischemic osteonecrosis in juvenile mouse - Huang, Qian; Zhang, Yuchen; Tang, Shengping; Zheng, Xinda; Li, Boxiang; Liu, Yun; Ding, Xiaofei; Zhao, Jinmin; Liu, Qian; Liao, Shijie (Frontiers in Nutrition, 2025)
Legg–Calvé–Perthes disease (LCPD) ranks as one of the most severe hip conditions that can lead to permanent deformity of the femoral head in children. Despite its severity, no effective pharmacological treatments are currently available, highlighting the urgent need for novel therapeutic agents. And platelet-derived growth factor-BB (PDGF-BB), a vital biological macromolecule, plays a critical role in vascular remodeling and bone regeneration, thereby establishing itself as a crucial drug target for activating bone repair. In this study, we demonstrate that biochanin A (BCA), a soybean-derived isoflavone, significantly prevents epiphyseal collapse and promotes bone regeneration in a juvenile ischemic osteonecrosis (JIO) model. Mechanistically, BCA enhances the formation of type H vessels in bone by indirectly facilitating the interaction between osteoclast precursors and endothelial cells, thereby accelerating bone repair in JIO. Specifically, BCA suppresses the differentiation of mature osteoclasts, expands the population of osteoclast precursors, and stimulates the secretion of PDGF-BB, which in turn promotes type H vessels angiogenesis. Our findings highlight the potential of BCA as a promising therapeutic candidate for the treatment of LCPD.